Invisible Giants. The Research Seminar as a Space of Interdisciplinary Convergence and Propitiation of Creative Research (I+C) (London Journal of Research In Humanities and Social Sciences, 2024)
Through the Mixed Realities research group of the Faculty of Design, Communication and Fine Arts, Pereira Section, of the Fundacin Universitaria del rea Andina, the research project creation (I+C) Invisible Giants was generated, whose objective is to understand why the monuments in the center of the city of Pereira have become a landscape and are invisible to the inhabitants and passers-by of the sector.All this mediated by the interdisciplinary convergence generated through the collaborative work of teachers and students of the Audiovisual and Digital Communication, Architecture and Animation Technology and Audiovisual Postproduction programs.
Keywords: Nikolai Marr; glottogenesis; labor; tool of labor; manual (linear; kinetic) language; sound language.; Convergence; Research Creation; Interdisciplinarity; Semillero.